Image correction for diffusion tensor imaging of Rhesus monkey thoracic spinal cord. Issue 6 (30th May 2019) - Rao, Jia‐Sheng; Liu, Zuxiang; Zhao, Can; Wei, Rui‐Han; Liu, Ruo‐Xi; Zhao, Wen; Zhou, Xia; Tian, Peng‐Yu; Yang, Zhao‐Yang; Li, Xiao‐Guang
Abstract: Background: The relatively tiny spinal cord of non‐human primate (NHP) causes increased challenge in diffusion tensor imaging (DTI) post‐processing. This study aimed to establish a reliable correction strategy applied to clinical DTI images of NHP. Methods: Six normal and partial spinal cord injury (SCI) rhesus monkeys underwent 3T MR scanning. A correction strategy combining multiple iterations and non‐rigid deformation was used for DTI image post‐processing. Quantitative evaluations were then conducted to investigate effects of distortion correction. Results: After correction, longitudinal geometric distortion, global distortion, and residual distance errors were all significantly decreased ( P < 0.05). Fractional anisotropy at the injured site was remarkably lower than that at the contralateral site ( P = 0.0488) and was substantially lower than those at the adjacent superior ( P = 0.0157) and inferior ( P = 0.0128) areas at the same side. Conclusions: Our image correction strategy can improve the quality of the DTI images of NHP thoracic cords, contributing to the development of SCI preclinical research.